Pengolahan Sampah Organik di Bank Sampah Kelurahan Setiamulya - Taufiqurrahman, Imam; Ifkar Usrah; Firmansyah MSN (LPPM UPN Veteran Jakarta, 2023)
Setiamulya Village is one of the villages that has a Cooperation Agreement (PKS) with the Faculty of Engineering, Siliwangi University. Through PKS, the Faculty of Engineering, Siliwangi University is committed to developing and overcoming problems in society through knowledge developed on campus. The Waste Bank is one of the solutions for the community in Setiamulya Village to overcome the waste problem that occurs in the environment. In its implementation so far, the Setiamulya Village waste bank has carried out the process of separating and storing recyclable waste for further distribution to parties who will recycle the waste. However, due to limitations, the organic waste in the waste bank cannot be utilized. so accumulation still often occurs. With this community service community partnership program, the Setiamulya Village waste bank community group will be provided with knowledge and facilities for processing organic waste through maggot cultivation. So that the organic waste in the waste bank can increase its economic value.